FEATURES OF NATURAL SEED REGENERATION IN FRESH MAPLE-LIME OAK FOREST IN THE LEFT-BANK FOREST-STEPPE - Tkach, V. P.; Rumyantsev, M. G.; Chygrynets, V. P.; Luk’yanets, V. A.; Kobets, O. V. (Forestry and Forest Melioration, 2018)
Introduction Today and in the near future, the frames after continuous fellings will dominate in silvicultural fund of the Left-bank Forest-Steppe. In oak forests of the region the principal forest-forming tree species, which forestry is focused on, are Quercus robur L. and Fraxinus excelsior L. The initial density of partial forest plantations will depend on the number of these species in the structure of regeneration. Therefore, the study of accompanying and subsequent natural regeneration in the region is a vital question and is of great practical importance. Materials and Methods During the research, the method of accounting for natural regeneration developed by URIFFM is used. The advance growth was distributed by species, groups of height, age and state of vitality. Over 200 discount areas (10 m2 each) were generally established. The scale developed by URIFFM is applied for assessment of success of natural regeneration. Results After final felling, the total number of regeneration in experiment 1 is 90.30 thousand pcs?ha-1, in experiment 2 it is 9.96 thousand pcs?ha-1. The proportion of principal forest forming species reaches 90.0 and 91.6 %, respectively. The placement by area is uniform (the frequency is 100 %). The success of natural regeneration is «successful». In the first year after clear felling, the total number of regeneration varies from 14.95 to 28.28 thousand pcs?ha-1 on the areas which are completely left under natural regeneration. The mostly reafforested are associate species (ash, maple (Acer platanoides L.) and field maple (Acer campestre L.), the proportion of which varies from 77.3 to 81.6 %. On the area where felling was made two years ago, the largest share of regeneration in the total number (13.10 thousand pcs?ha-1) belongs to oak (48.1 %). The proportion of ash is 15.6 %, maple 22.9 %, field maple 12.6 % and lime 0.8 % only. On the sites of partial forest plantations of oak with the scheme of placement 6 ? 0.7 m, the number of natural regeneration in row-spacings in one-year cultures is 30.67 thousand pcs?ha-1, in two-year it is 13.13 thousand pcs?ha-1 and in three-year 9.00 thousand pcs?ha-1, including the principal species (an oak and an ash) 14.20, 6.33 and 4.60 thousand pcs?ha-1, respectively. Conclusions The research results evidence that it is possible to regenerate oak forests in natural way under the realization of purposeful management actions. Thus it is certainly necessary to take into account periodicity of fruiting of oak, and do the final felling in the year of a good fruiting of oak or on the next year. In such cases there is a sufficient number of regular advance growth of oak.